Bulletproof plug board and manufacturing method thereof
By adopting a combined structure of ceramic material layer, alloy layer, anti-depression layer, energy-absorbing layer and UD plate layer in the bulletproof insertion plate, combined with the in-situ composite technology of 3D printed honeycomb structure and Kevlar material, the existing bulletproof insertion plate has solved the problems of large weight and low protection performance, and achieved efficient energy absorption and lightweight bulletproof effects.
Patent Information
- Application Number
- CN202510044431.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-11
- Publication Date
- 2025-05-09
AI Technical Summary
The existing bulletproof insert plates are relatively large in weight and have low protective performance, which is especially difficult to protect the penetration of Type 53 7.62mm pyrobulins and 6.8mm and 8.6mm light weapons with initial velocity of 880m/s or above.
The bulletproof insertion plate consisting of a ceramic material layer, an alloy layer, an anti-depression layer, an energy-absorbing layer and a UD plate layer is adopted. The energy-absorbing layer includes a 3D printed and formed honeycomb structure titanium alloy material layer and a Kevlar material layer. The two are combined in situ into an integrated structure, and the connection strength is enhanced through a three-stage pressure bonding process.
It achieves significant improvement in bulletproof performance while maintaining lightweight, can effectively absorb energy and attenuate impact pressure, prevent the penetration of high-speed ammunition, and exhibit good protective effects under different environmental conditions.
Smart Images

Figure CN119958378A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of bulletproof plug plates, and in particular to a bulletproof plug plate and a manufacturing method thereof. Background Art
[0002] As an important protective unit for individual bulletproof, the material system of bulletproof plates has evolved from ancient rattan and leather materials to bronze armor, and later developed into metal-based armor. It has been developed into protective materials based on Kevlar, the aramid fiber invented by DuPont, and UHMWPE, an ultra-molecular weight polyethylene fiber composite material invented by the Dutch, which has always attracted global attention.
[0003] In recent years, due to the continuous upgrading of strategic weapons, the demand for bulletproof inserts has increased. For example, the XM5 rifle and the XM250 squad machine gun fire the new 6.8x51mm high-pressure, high-speed ammunition designed by SIG Sauer. This ammunition uses a hybrid structure metal cartridge and is fired from a 16-inch (406mm) long barrel. It can allow a 135-grain (8.75-gram) projectile to reach an initial velocity of 3,000 feet per second (914 meters per second) and a muzzle energy of approximately 2,700 feet pounds (3,661 joules). This is a high-power, high-velocity, lightweight ammunition with a low-reaching trajectory and quite strong armor-piercing ability. The introduction of the new 6.8mm caliber bullet has put forward higher requirements on the protective capability of the bulletproof insert. Through the evolution of the material system, it can be seen that lightweight and functionalization are the unchanging themes of individual protective equipment, and the effective combination of different materials is the key effect to improve the bulletproof function and weight bottleneck constraints of the bulletproof insert. Therefore, individual protective equipment with good protective performance and light weight plays a very important role.
[0004] In recent years, many experts and scholars have conducted relevant research in this regard. However, it is unable to protect against the penetration of Type 53 7.62mm incendiary bullets with an initial velocity of more than 880m / s, especially against light weapons with an initial velocity of 6.8mm and 934m / s and 8.6mm and 950±10m / s. Summary of the invention
[0005] The object of the present invention is to provide a bulletproof plug plate and a manufacturing method thereof, so as to solve the problem that the existing bulletproof plug plate is heavy and has low protective performance. Another object of the present invention is to solve the problem that the bulletproof plug plate is difficult to effectively protect against the penetration of Type 53 7.62mm incendiary bullets with an initial velocity of more than 880m / s, especially against 6.8mm light weapons with an initial velocity of 934m / s and 8.6mm light weapons with an initial velocity of 950±10m / s.
[0006] The technical solution adopted in this application to solve this technical problem is:
[0007] A bulletproof insert plate, comprising a ceramic material layer, an alloy layer, an anti-sag layer, an energy absorbing layer and a UD plate layer which are sequentially layered;
[0008] The energy absorbing layer comprises a titanium alloy material layer with a honeycomb structure and a Kevlar material layer with a honeycomb structure, the titanium alloy material layer is formed by 3D printing, the Kevlar material layer is 3D printed directly on the titanium alloy material layer, and the titanium alloy material layer and the Kevlar material layer are in-situ composited into an integrated structure.
[0009] Furthermore, the thickness of the honeycomb structure is 2mm-4mm, the pore size of the honeycomb structure is 2mm-8mm, and the honeycomb structure is filled with energy-absorbing material.
[0010] Furthermore, crack-stopping layers are connected to two side surfaces of the ceramic material layer. The crack-stopping layers are lamellar materials made of Kevlar fibers, and the thickness of the crack-stopping layers is 1 mm-1.2 mm.
[0011] Furthermore, the alloy layer is an α+β dual-phase titanium alloy, the elongation at break of the alloy layer is greater than 8%, the tensile strength of the alloy layer is greater than 1700 MPa, and the thickness of the alloy layer is 3 mm-5 mm.
[0012] Furthermore, a carbon nanotube-polyurea resin coating is provided on two side surfaces of the alloy layer, and the thickness of the carbon nanotube-polyurea resin coating is 2 mm-5 mm.
[0013] A method for manufacturing a bulletproof insert comprises the following steps:
[0014] Step S1: preparing materials, respectively preparing materials for a ceramic material layer, an alloy layer, an anti-sag layer, an energy absorption layer and a UD plate layer, and preparing a crack arrest layer on both sides of the ceramic material layer and a carbon nanotube-polyurea resin coating on both sides of the alloy layer for later use;
[0015] Step S2: Compounding and hot pressing, using an adhesive to sequentially bond the ceramic material layer, alloy layer, anti-sag layer, energy absorption layer and UD sheet layer obtained in step S1 to form a composite board, heating and hot pressing in a pressing mold in three stages, the heating rate of the three stages is 2°C / min, wherein, in the first stage, the mold is heated to 80°C-100°C, and the pressure is 5MPa-15MPa; in the second stage, the mold is heated to 100°C-160°C, and the pressure is 12MPa-18MPa; in the third stage, the mold is heated to 140°C-170°C, and the pressure is 15MPa-25MPa. After the hot pressing is completed, the heat and pressure are maintained for 20min-90min, and the pressure is released after the temperature drops to 20°C-40°C to obtain an insert sheet;
[0016] Step S3: heat setting, placing the plug plate obtained in step S2 in a plug plate mold, keeping the temperature and pressure in an autoclave at 80°C-140°C for 45min-120min to melt the ultra-high molecular weight polyethylene, taking it out after cooling, and wrapping it with an edge sealing layer to obtain a bulletproof plug plate.
[0017] Furthermore, the preparation method of the alloy layer is as follows: take a 4mm-6mm titanium alloy plate, heat it to 800℃-1060℃, and use a roller press to roll it with a rolling pressure of 3.5MPa-9MPa and a rolling speed of 350mm / s-500mm / s until the thickness of the titanium alloy plate is 3mm-5mm.
[0018] Furthermore, the preparation method of the carbon nanotube-polyurea resin coating is as follows: 15%wt-30%wt of carbon nanotubes are added to the polyurea resin, wherein the specification of the carbon nanotubes is 25nm-40nm, and the carbon nanotube-polyurea resin coating is obtained by uniformly dispersing the carbon nanotube-polyurea resin coating; the carbon nanotube-polyurea resin coating is uniformly sprayed on the front and back surfaces of the alloy layer using a high-pressure spray gun, and the carbon nanotube-polyurea resin coating is obtained after curing.
[0019] Furthermore, the preparation method of the UD sheet layer is as follows: select a surface density of 80g / m 2 -120g / m 2 The ultra-high molecular weight polyethylene UD cloth is dipped in glue and laid flat for 12-15 layers, with the outermost layer being kevlar fiber cloth. The UHMWPE fiber backboard is formed by vacuum hot pressing in an autoclave to obtain the UD sheet layer.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The overall design concept of the present invention mainly includes three points. First, in view of the high kinetic energy of high-speed bullets, an energy-absorbing layer is set to focus on improving the energy absorption and impact resistance. Second, the integrated design concept of the plug plate adopts boron nitride ceramic plates and titanium alloy plates to achieve double bulletproof functions, plus an anti-sag cushion layer, and is designed as a whole. Third, a new material process of using 3D printing titanium alloy honeycomb structure and adding Kevlar composite material honeycomb structure on the honeycomb structure is used. In addition, the present invention adopts a three-stage pressure bonding process, and the connection strength is better.
[0022] The present invention is provided with a honeycomb energy-absorbing layer, which can significantly reduce the impact pressure of key parts. Under the same impact conditions, the honeycomb energy-absorbing layer of the present invention can absorb energy more effectively. The honeycomb structure is filled with energy-absorbing materials, and the effect is further improved.
[0023] The present invention arranges crack-stop layers on two sides of the ceramic material layer, which can effectively prevent the ceramic material from bursting after being subjected to impact, and bind the ceramic material inside the crack-stop layer, thereby improving its continuous bulletproof capability.
[0024] The alloy layer of the present invention is an α+β dual-phase titanium alloy, which has the characteristics of high strength and high toughness, good comprehensive performance, good organizational stability, high tensile strength and yield strength, and the tensile strength after aging can reach 1500-2000MPa. After the surface is coated with a carbon nanotube-polyurea resin coating, it has excellent waterproof, corrosion-resistant, wear-resistant, erosion-resistant, bullet-proof and explosion-proof properties, and also improves the bonding strength with other layer structures. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a layer structure diagram of the present invention;
[0026] Figure 2 is a physical diagram of the bulletproof insert of the present invention;
[0027] Figure 3 This is a state diagram of the bulletproof plug plate of the third embodiment of the present invention after ballistic detection.
[0028] The numbers in the attached drawings are: 1. edge sealing layer; 2. crack arrest layer; 3. ceramic material layer; 4. carbon nanotube-polyurea resin coating; 5. alloy layer; 6. anti-sag layer; 7. energy absorption layer; 8. titanium alloy material layer; 9. Kevlar material layer; 10. UD sheet layer; 11. Kevlar fiber cloth; 12. UD cloth. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0030] like Figure 1 and Figure 2 As shown, a bulletproof insert comprises a ceramic material layer 3 made of boron nitride, an alloy layer 5 made of titanium alloy, an anti-sag layer 6 made of fiber cloth, a honeycomb energy absorption layer 7 and a UD plate layer 10, which are sequentially layered, and each layer structure is hot-pressed and bonded by an adhesive and wrapped with an edge sealing layer 1.
[0031] The thickness of the ceramic material layer 3 is 5mm-9mm, and the two sides of the ceramic material layer 3 are connected with a lamellar crack-stopping layer 2 made of Kevlar fiber. The thickness of the crack-stopping layer 2 is 1mm. Because of the coating of the Kevlar fiber material, the boron nitride ceramic is not easy to break, or in other words, even if it breaks, it is not easy to fall off and can still remain on the bulletproof plug plate, having a continuous bulletproof effect.
[0032] The alloy layer 5 is an α+β dual-phase titanium alloy with a thickness of 3 mm to 5 mm. The elongation at break of the alloy layer 5 is greater than 8% and the tensile strength is greater than 1700 MPa.
[0033] Carbon nanotube-polyurea resin coating 4 is provided on both sides of the alloy layer 5. In the carbon nanotube-polyurea resin coating 4, carbon nanotubes account for 15%-30% of the weight of polyurea resin. The thickness of the carbon nanotube-polyurea resin coating 4 is 2mm-5mm.
[0034] The anti-sag layer 6 is a fiber cloth made of fiber material impregnated with adhesive, with a single layer thickness of 0.2 mm-0.22 mm, and 4-6 layers are laid.
[0035] The energy absorbing layer 7 comprises a titanium alloy material layer 8 and a Kevlar material layer 9, both of which are honeycomb structures formed by 3D printing. The bottom layer of the honeycomb structure is a titanium alloy material layer 8 processed by 3D printing in a honeycomb shape, with a thickness of 1mm-1.8mm. The surface layer is made of Kevlar material directly 3D printed on the surface of the titanium alloy material layer 8 in a honeycomb shape. The Kevlar material layer 9 and the titanium alloy material layer 8 form an in-situ composite integrated structure. The thickness of the honeycomb structure is 2mm-4mm, and the pore diameter of the honeycomb structure is 2mm-8mm. The honeycomb structure is filled with energy absorbing material, which can greatly attenuate the impact pressure of key parts and can effectively absorb energy under the same impact.
[0036] The adhesive is any one of epoxy adhesive, polyurethane adhesive, polyacrylic adhesive or organic silicone adhesive.
[0037] Example 1
[0038] Preparation:
[0039] In the first step, a 5.5 mm boron nitride curved surface ceramic plate is used as the ceramic material layer 3, and a 1 mm thick crack arresting layer 2 made of a kevlar fiber material is laminated on both sides in a 200-liter autoclave, and the plate is cooled and then used for later use;
[0040] In the second step, a 6mm thick titanium alloy plate was taken and heated to 1060℃, then taken out and rolled in a roller press to a thickness of 3.5±0.05mm, with a rolling pressure of 3.5MPa and a rolling speed of 370mm / s. The improved α+β dual-phase titanium alloy material has a tensile strength of 1700MPa after aging, and a measured density of 4.51g / cm 3 The elongation of the α+β dual-phase titanium alloy material is greater than 8%, and the measured elongation (50 mm gauge length) can be ensured to be above 10%. Then it is cut into the required size of the bulletproof curved surface on a laser cutting machine as the alloy layer 5 for standby use.
[0041] The third step is to spray a 2 mm thick carbon nanotube-polyurea resin coating 4 on the surface of the alloy layer 5. The carbon nanotube-polyurea resin coating 4 is prepared by adding 15%wt carbon nanotubes to the polyurea resin. The carbon nanotubes are 25 nanometers in size and are evenly dispersed at a speed of 12000r / min. The high-pressure special spray gun is used to evenly spray the front and back surfaces of the alloy layer 5 to prepare a polymer carbon nanotube composite material, which is a polymer material composited with carbon nanotube materials. It has excellent waterproof, anti-corrosion, weather-resistant, super wear-resistant, anti-scouring, impact-resistant, bullet-proof, explosion-proof and other properties.
[0042] The fourth step is to prepare the anti-sag layer 6 by stacking five layers of purchased 0.2 mm fiber cloth, dipping both sides with glue, and then pressing them together with a curved panel of the same size to form a mat as an anti-sag cushion layer for standby use.
[0043] The fifth step is to use the energy-absorbing layer 7, an in-situ structurally integrated honeycomb structure. The bottom layer is a titanium alloy material layer 8, which is processed into a honeycomb structure by 3D printing with a thickness of 1.2 mm. The surface layer is a Kevlar material layer 9, which is also realized by 3D printing. The Kevlar material layer 9 is directly printed on the surface of the titanium alloy material layer 8 with a thickness of 1.3 mm. The pore size of the honeycomb structure is 2 mm-8 mm. The energy absorption effect is achieved by changing the texture and porosity of the honeycomb structure in the radial and axial directions, which greatly attenuates the impact pressure at key parts and effectively absorbs energy under the same impact conditions.
[0044] Step 6: Preparation of UD sheet layer 10: a UD sheet with a surface density of 100 g / m 2 The UD cloth 12 impregnated with water-soluble epoxy resin is laid flat on a cutting machine, and is cut into the required size of the curved bulletproof insert using a fully automatic cutting machine. The cut pieces are laid in 12 layers, and the surface is covered with Kevlar fiber cloth 11. After weighing, it is vacuum pressed in an autoclave to obtain a UHMWPE fiber backboard, that is, the material of the UD board layer 10.
[0045] Composite hot pressing:
[0046] The seventh step is edge sealing and compounding. The materials prepared in each of the above steps are cleaned of impurities and edge sealed. The ceramic material layer 3, alloy layer 5, anti-sag layer 6, energy absorption layer 7 and UD plate layer 10 are sequentially stacked and connected. When connecting, epoxy adhesive is applied on both sides of each layer and pressed. The pressing process is as follows: the boron nitride curved surface ceramic plate with a crack-stop layer 2 made of double-sided composite kevlar fiber is used as the first layer of the bullet-facing surface in a 200-liter autoclave; the titanium alloy curved plate sprayed with nanotube material is used as the second protective layer; and the anti-sag cushion layer is used as the third layer; The titanium alloy material layer and Kevlar material layer of the prefabricated honeycomb structure are used as the fourth layer; the UD sheet layer 10 is used as a close-fitting protective layer, and are put into the pressing mold together, and undergo three stages of heating and pressurization in the autoclave, wherein in the first stage, the mold is heated to 90°C and the pressure is 7MPa; in the second stage, the mold is heated to 110°C and the pressure is 15MPa; in the third stage, the mold is heated to 145°C and the pressure is 15MPa; after the three-stage operation is completed, the heat and pressure are maintained for 25 minutes, and when the temperature drops to 30°C, the insert sheet is taken out.
[0047] Heat Setting:
[0048] In the eighth step, the plug plate is sealed in a vacuum bag and placed in a plug plate mold, and kept in an autoclave at 80° C. to 140° C. for 45 min to 120 min, so that the UHMWPE is melted by heat, and a better heat setting state is that no melt is seen at the edge of the bulletproof plug plate, and no processing or trimming is required; after cooling, the edge is sealed with Oxford cloth as the edge sealing layer 1, and the bulletproof plug plate is obtained.
[0049] Detection:
[0050] The weight of the bulletproof plate is 2590g and the thickness is 22.3mm. After the 53-type 7.62mm ballistic gun test, 3 shots were fired at 15 meters using 7.62mm armor-piercing incendiary bullets, with initial velocities of 877m / s, 883m / s and 879m / s respectively, and the bulges of the bulletproof plate were 18.7mm, 25.6mm, and 23.2mm. Two more shots were fired using the 95-type 5.8mm armor-piercing bullets, with initial velocities of 926m / s and 934m / s, and the bulges of the bulletproof plate were 21.3mm and 22.9mm. After heating at 70℃ for 24 hours, the bullets were Using 7.62mm armor-piercing incendiary bullets, three shots were fired at 15 meters, with initial velocities of 878m / s, 881m / s and 885m / s respectively, and the bulges of the bulletproof plate were 22.6mm, 24.3mm and 24.1mm; after being kept at a low temperature of -55℃ for 24 hours, using 7.62mm armor-piercing incendiary bullets, three shots were fired at 15 meters, with initial velocities of 879m / s, 877m / s and 862m / s respectively, and the bulges of the bulletproof plate were 24.8mm, 28.3mm and 29.1mm.
[0051] Example 2
[0052] Preparation:
[0053] In the first step, a 6.0 mm thick boron nitride curved surface ceramic plate is used as the ceramic material layer 3, and a 1 mm thick crack arresting layer 2 made of a kevlar fiber material is laminated on both sides in a 200 liter autoclave, and the plate is cooled and then used for later use;
[0054] In the second step, a 6mm thick titanium alloy plate was taken and heated to 1060℃, then taken out and rolled in a roller press to a thickness of 3.8±0.05mm, with a rolling pressure of 4.2MPa and a rolling speed of 420mm / s. The improved α+β dual-phase titanium alloy material had a tensile strength of 1820MPa after aging, and a measured density of 4.49g / cm 3 The elongation of the α+β dual-phase titanium alloy material is greater than 8%, and the measured elongation (50 mm gauge length) can be ensured to be above 10%. Then it is cut into the required size of the bulletproof curved surface on a laser cutting machine as the alloy layer 5 for standby use.
[0055] The third step is to spray a 2.5 mm thick carbon nanotube-polyurea resin coating 4 on the surface of the alloy layer 5. The carbon nanotube-polyurea resin coating 4 is made by adding 15%wt carbon nanotubes to the polyurea resin. The carbon nanotubes are 30 nanometers in size and are evenly dispersed at a speed of 15,000 r / min. The high-pressure special spray gun is used to evenly spray the front and back surfaces of the alloy layer 5 to prepare a polymer carbon nanotube composite material, which is a polymer material composited with carbon nanotube materials. It has excellent waterproof, anti-corrosion, weather-resistant, super wear-resistant, anti-scouring, impact-resistant, bullet-proof, explosion-proof and other properties.
[0056] The fourth step is to prepare the anti-sag layer 6 by stacking six layers of purchased 0.22 mm fiber cloth, dipping both sides with glue, and then pressing them together with a curved panel of the same size to form a mat as an anti-sag cushion layer for standby use.
[0057] The fifth step is to use the energy-absorbing layer 7, an in-situ structurally integrated honeycomb structure. The bottom layer is a titanium alloy material layer 8, which is processed into a honeycomb structure by 3D printing with a thickness of 1.5 mm. The surface layer is a Kevlar material layer 9, which is also realized by 3D printing with a thickness of 1.5 mm. The pore size of the honeycomb structure is 2 mm-8 mm. The energy absorption effect is achieved by changing the texture and porosity of the honeycomb structure in the radial and axial directions, which greatly attenuates the impact pressure at key parts and effectively absorbs energy under the same impact conditions.
[0058] Step 6: Preparation of UD sheet layer 10: a UD sheet with a surface density of 118 g / m 2The UD cloth 12 impregnated with water-soluble epoxy resin is laid flat on a cutting machine and cut into the required size of the curved bulletproof insert using a fully automatic cutting machine. The cut pieces are laid in 15 layers and the surface is covered with Kevlar fiber cloth 11. After weighing, the pieces are vacuum pressed in an autoclave to obtain a UHMWPE fiber backboard, i.e., the material of the UD board layer 10.
[0059] Composite hot pressing:
[0060] The seventh step is edge sealing and compounding. The materials prepared in each of the above steps are cleaned of impurities on the surface and sealed. The ceramic material layer 3, alloy layer 5, anti-sag layer 6, energy absorption layer 7 and UD plate layer 10 are sequentially stacked and connected. When connecting, epoxy adhesive is applied on both sides of each layer and pressed. The pressing process is as follows: the boron nitride curved surface ceramic plate with a crack-stop layer 2 made of double-sided composite kevlar fiber is used as the first layer of the bullet-facing surface in a 200-liter autoclave; the titanium alloy curved plate sprayed with nanotube material is used as the second protective layer; the anti-sag cushion layer is used as the third layer; pre- The titanium alloy material layer and the Kevlar material layer of the honeycomb structure are used as the fourth layer; the UD plate layer 10 is used as a close-fitting protective layer, and are put into a pressing mold together, and undergo three stages of heating and pressurization in the autoclave, wherein in the first stage, the mold is heated to 95°C and the pressure is 8.5MPa; in the second stage, the mold is heated to 120°C and the pressure is 15MPa; in the third stage, the mold is heated to 155°C and the pressure is 16MPa; after the three-stage operation is completed, the heat and pressure are maintained for 40 minutes, and the composite plate is taken out when the temperature drops to 30°C.
[0061] Heat setting:
[0062] In the eighth step, the plug plate is sealed in a vacuum bag and placed in a plug plate mold, and kept in an autoclave at 80° C. to 140° C. for 45 min to 120 min, so that the UHMWPE is melted by heat, and a better heat setting state is that no melt is seen at the edge of the bulletproof plug plate, and no processing or trimming is required; after cooling, the edge is sealed with Oxford cloth as the edge sealing layer 1, and the bulletproof plug plate is obtained.
[0063] The weight of the bulletproof plate is 2598g and the thickness is 22.6mm. After the 53-type 7.62mm ballistic gun test, 3 shots were fired at 15 meters using 7.62mm armor-piercing incendiary bullets, with the initial velocities of the bullets being 883m / s, 876m / s and 879m / s respectively, and the bulges of the bulletproof plate were 27.3mm, 21.7mm, and 24.2mm. The 95-type 5.8mm armor-piercing bullets were used for 3 shots, with the initial velocities of the bullets being 916m / s, 924m / s, and 927m / s, and the bulges of the bulletproof plate were 23.3mm, 26.9mm, and 27.8mm. After heating at 70℃ After keeping warm for 24 hours, 3 shots were fired at 15 meters using 7.62mm armor-piercing incendiary bullets. The initial velocities of the bullets were 877m / s, 879m / s and 873m / s respectively, and the bulges of the bulletproof plate were 24.6mm, 26.3mm and 27.1mm. After keeping warm at -55℃ for 24 hours, 3 shots were fired at 15 meters using 7.62mm armor-piercing incendiary bullets. The initial velocities were 877m / s, 879m / s and 871m / s respectively, and the bulges of the bulletproof plate were 34.8mm, 29.4mm and 32.9mm.
[0064] Example 3
[0065] Preparation:
[0066] In the first step, a 6.5 mm thick boron nitride curved ceramic plate is used as the ceramic material layer 3, and a 1 mm thick crack arresting layer 2 made of a kevlar fiber material is laminated on both sides in a 200 liter autoclave, and the plate is cooled and then used for later use;
[0067] In the second step, a 6mm thick titanium alloy plate was taken and heated to 1060℃, then taken out and rolled in a roller press to a thickness of 4.2±0.05mm, with a rolling pressure of 4.2MPa and a rolling speed of 420mm / s. The improved α+β dual-phase titanium alloy material had a tensile strength of 1920MPa after aging, and a measured density of 4.51g / cm 3 The elongation of the α+β dual-phase titanium alloy material is greater than 8%, and the measured elongation (50 mm gauge length) can be ensured to be above 10%. Then it is cut into the required size of the bulletproof curved surface on a laser cutting machine as the alloy layer 5 for standby use.
[0068] The third step is to spray a 2.8 mm thick carbon nanotube-polyurea resin coating 4 on the surface of the alloy layer 5. The carbon nanotube-polyurea resin coating 4 is prepared by adding 15%wt carbon nanotubes to the polyurea resin. The carbon nanotubes are 40 nanometers in size and are evenly dispersed at a speed of 15000r / min. The high-pressure special spray gun is used to evenly spray the front and back surfaces of the alloy layer 5 to prepare a polymer carbon nanotube composite material, which is a polymer material composited with carbon nanotube materials. It has excellent waterproof, anti-corrosion, weather-resistant, super wear-resistant, anti-scouring, impact-resistant, bullet-proof, explosion-proof and other properties.
[0069] The fourth step is to prepare the anti-sag layer 6 by stacking four layers of purchased 0.22 mm fiber cloth, dipping both sides with glue, and then pressing them together with a curved panel of the same size to form a mat as an anti-sag cushion layer for standby use.
[0070] The fifth step is to use the energy-absorbing layer 7, an in-situ structurally integrated honeycomb structure. The bottom layer is a titanium alloy material layer 8, which is processed into a honeycomb structure by 3D printing with a thickness of 1.8 mm. The surface layer is a Kevlar material layer 9, which is also realized by 3D printing with a thickness of 1.8 mm. The pore size of the honeycomb structure is 2 mm-8 mm. The energy absorption effect is achieved by changing the texture and porosity of the honeycomb structure in the radial and axial directions, which greatly attenuates the impact pressure at key parts and effectively absorbs energy under the same impact conditions.
[0071] Step 6: Preparation of UD sheet layer 10: prepare a UD sheet layer 10 with a surface density of 112 g / m 2 The UD cloth 12 impregnated with water-soluble epoxy resin is laid flat on a cutting machine, and is cut into the required size of the curved bulletproof insert using a fully automatic cutting machine. The cut pieces are laid in 12 layers, and the surface is covered with Kevlar fiber cloth 11. After weighing, it is vacuum pressed in an autoclave to obtain a UHMWPE fiber backboard, that is, the material of the UD board layer 10.
[0072] Composite hot pressing:
[0073] The seventh step is edge sealing and compounding. The materials prepared in each of the above steps are cleaned of impurities on the surface and sealed. The ceramic material layer 3, alloy layer 5, anti-sag layer 6, energy absorption layer 7 and UD plate layer 10 are sequentially stacked and connected. When connecting, epoxy adhesive is applied on both sides of each layer and pressed. The pressing process is as follows: the boron nitride curved surface ceramic plate with a crack-stop layer 2 made of double-sided composite kevlar fiber is used as the first layer of the bullet-facing surface in a 200-liter autoclave; the titanium alloy curved plate sprayed with nanotube material is used as the second protective layer; the anti-sag cushion layer is used as the third layer; pre- The titanium alloy material layer and the Kevlar material layer of the honeycomb structure are used as the fourth layer; the UD plate layer 10 is used as a close-fitting protective layer, and are put into a pressing mold together, and undergo three stages of heating and pressurization in the autoclave, wherein in the first stage, the mold is heated to 98°C and the pressure is 8.5MPa; in the second stage, the mold is heated to 125°C and the pressure is 15MPa; in the third stage, the mold is heated to 160°C and the pressure is 16MPa; after the three-stage operation is completed, the heat and pressure are maintained for 60 minutes, and the composite plate is taken out when the temperature drops to 30°C.
[0074] Heat setting:
[0075] In the eighth step, the plug plate is sealed in a vacuum bag and placed in a plug plate mold, and kept in an autoclave at 80° C. to 140° C. for 45 min to 120 min, so that the UHMWPE is melted by heat, and a better heat setting state is that no melt is seen at the edge of the bulletproof plug plate, and no processing or trimming is required; after cooling, the edge is sealed with Oxford cloth as the edge sealing layer 1, and the bulletproof plug plate is obtained.
[0076] The weight of the bulletproof insert is 2655g and the thickness is 22.8mm. After the ballistic gun test, the state of the bulletproof insert is as follows: Figure 3 As shown, 6 shots were fired at 15 meters using a US 6.8mm armor-piercing projectile, with initial velocities of 934m / s, 940m / s, 936m / s, 934m / s, 935m / s, 938m / s, respectively. The bulges of the bulletproof plate were 29.3mm, 24.7mm, 23.6mm, 28.2mm, 28.9mm, 24.4mm. After heating at 70℃ for 24h, the US 6.8mm armor-piercing projectile was fired at 1 Three shots were fired at 5 meters, with initial velocities of 936m / s, 939m / s and 943m / s respectively, and the bulges of the bulletproof plate were 24.2mm, 25.3mm and 27.3mm; after being kept at a low temperature of -55℃ for 24 hours, three shots were fired at 15 meters using American 6.8mm armor-piercing bullets, with initial velocities of 937m / s, 941m / s and 946m / s respectively, and the bulges of the bulletproof plate were 25.8mm, 29.2mm and 30.9mm.
[0077] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
Claims
1. A bulletproof insert, characterized in that: It comprises a ceramic material layer (3), an alloy layer (5), an anti-sag layer (6), an energy absorption layer (7) and a UD plate layer (10) which are sequentially layered; The energy absorbing layer (7) comprises a titanium alloy material layer (8) having a honeycomb structure and a Kevlar material layer (9) having a honeycomb structure, and the titanium alloy material layer (8) and the Kevlar material layer (9) are composited into an integral structure.
2. The bulletproof insert according to claim 1, characterized in that: The thickness of the honeycomb structure is 2mm-4mm, the pore diameter of the honeycomb structure is 2mm-8mm, and the honeycomb structure is filled with energy absorbing material.
3. The bulletproof insert according to claim 1, characterized in that: The two sides of the ceramic material layer (3) are connected to a crack-stopping layer (2), the crack-stopping layer (2) is a sheet-like material made of Kevlar fiber, and the thickness of the crack-stopping layer is 1 mm-1.2 mm.
4. The bulletproof insert according to claim 1, characterized in that: The alloy layer (5) is an α+β dual-phase titanium alloy, the elongation at break of the alloy layer (5) is greater than 8%, the tensile strength of the alloy layer (5) is greater than 1700 MPa, and the thickness of the alloy layer (5) is 3 mm-5 mm.
5. The bulletproof insert according to claim 1, characterized in that: Carbon nanotube-polyurea resin coatings (4) are provided on two side surfaces of the alloy layer (5), and the thickness of the carbon nanotube-polyurea resin coatings (4) is 2 mm to 5 mm.
6. A method for manufacturing a bulletproof plug plate, used for manufacturing the bulletproof plug plate according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step S1: preparing materials, respectively preparing materials for a ceramic material layer (3), an alloy layer (5), an anti-sag layer (6), an energy absorption layer (7) and a UD plate layer (10), and preparing a crack arrest layer (2) on both sides of the ceramic material layer (3), and preparing a carbon nanotube-polyurea resin coating (4) on both sides of the alloy layer (5), and setting them aside; Step S2: Compounding and hot pressing, using an adhesive to sequentially bond the ceramic material layer (3), alloy layer (5), anti-sag layer (6), energy absorption layer (7) and UD sheet layer (10) obtained in step S1 to form a composite board, and heating and hot pressing in a pressing mold in three stages, the heating rate of the three stages is 2°C / min, wherein in the first stage, the mold is heated to 80°C to 100°C, and the pressure is 5MPa to 15MPa; in the second stage, the mold is heated to 100°C to 160°C, and the pressure is 12MPa to 18MPa; in the third stage, the mold is heated to 140°C to 170°C, and the pressure is 15MPa to 25MPa. After the hot pressing is completed, the heat and pressure are maintained for 20min to 90min, and the pressure is released after the temperature drops to 20°C to 40°C, thereby obtaining an insert sheet; Step S3: heat setting, placing the plug plate obtained in step S2 in a plug plate mold, keeping the temperature and pressure in an autoclave at 80°C-140°C for 45min-120min to melt the ultra-high molecular weight polyethylene, taking it out after cooling, and wrapping it with an edge sealing layer (1) to seal the edges to obtain a bulletproof plug plate.
7. The method for manufacturing a bulletproof insert according to claim 6, characterized in that: The preparation method of the alloy layer (5) is as follows: take a 4mm-6mm titanium alloy plate, heat it to 800℃-1060℃, and use a roller press to roll it at a rolling pressure of 3.5MPa-9MPa and a rolling speed of 350mm / s-500mm / s until the thickness of the titanium alloy plate is 3mm-5mm.
8. The method for manufacturing a bulletproof insert according to claim 6, characterized in that: The preparation method of the carbon nanotube-polyurea resin coating (4) is as follows: 15%wt-30%wt of carbon nanotubes are added to the polyurea resin, wherein the specification of the carbon nanotubes is 25nm-40nm, and the carbon nanotube-polyurea resin coating is obtained by uniformly dispersing the carbon nanotube-polyurea resin coating; the carbon nanotube-polyurea resin coating is uniformly sprayed on the front and back surfaces of the alloy layer (5) using a high-pressure spray gun, and the carbon nanotube-polyurea resin coating (4) is obtained after curing.
9. The method for manufacturing a bulletproof insert according to claim 6, characterized in that: The preparation method of the UD sheet layer (10) is as follows: selecting a surface density of 80 g / m 2 -120g / m 2 The ultra-high molecular weight polyethylene UD cloth is dipped in glue and laid flat in 12-15 layers, with the outermost layer being kevlar fiber cloth, and vacuum hot pressing is performed in an autoclave to form a UHMWPE fiber backboard, thus obtaining a UD sheet layer (10).
Citation Information
Cited By
Metal material and non-metal material combined part and preparation method thereof
CN120245406A